Arenesulfonyl Fluoride Synthesis via Copper‐free Sandmeyer‐type Fluorosulfonylation of Arenediazonium Salts. Issue 10 (2nd July 2020) - Lin, Qiongzhen; Ma, Zhanhu; Zheng, Changge; Hu, Xiao‐Jun; Guo, Yong; Chen, Qing‐Yun; Liu, Chao
Summary of main observation and conclusion: The limited availability of highly valuable arenesulfonyl fluorides seriously hinders their further application in many research fields including medicinal chemistry and chemical biological, organic synthesis, polymer preparation, etc . We report herein a mild and efficient copper‐free Sandmeyer‐type fluorosulfonylation reaction of various arenediazonium salts to prepare valuable arenesulfonyl fluorides using K2 S2 O5 as both a reductant and a practical sulfonyl source in combination with N ‐fluorobenzenesulfonimide as an effective fluorine source. This methodology provides an attractive route to diverse important arenesulfonyl fluorides given the overall practicality and scope. Abstract : A mild and efficient copper‐free Sandmeyer‐type fluorosulfonylation reaction of various arenediazonium salts was developed to prepare valuable arenesulfonyl fluorides using K2 S2 O5 as a practical sulfonyl source in combination with N ‐fluorobenzenesulfonimide as an effective fluorine source.